Auctions with Constrained Information: Blind Bidding for Motion Pictures - Blumenthal, Marsha A. (The Review of Economics and Statistics, 1988)
Toward explaining why movie exhibitors have sought legislation requiring distributors to trade-screen films before soliciting bids, a simulation of a Nash equilibrium in an auction suggests that without previews bidders may suffer losses i n expected utility. This supports the hypothesis that risk aversion a nd competition render exhibitors unable to reduce their bids enough t o compensate fully for the dearth of information. An error-components model is used to analyze a unique industry dataset. The results conf irm that a component of the bid is lower (raising mean return), while the variance of return is greater for blindly-licensed films. Copyright 1988 by MIT Press.